The improvement of biowaste management and utilization of a greenhouse tomato production plant : a case study - Podhradska, Alexandra; Christofi, Theodor (2023)
Agricultural waste that is daily generated in immense quantities poses an environmental, social as well as an economic burden if left untreated. The transformation to a sustainable circular bio-economy model is promoting the elimination of the mismanagement of agricultural waste by its valorisation though multiple different processes. For small and mid-size farmers anaerobic digestors for biogas production or aerobic composters for biofertilizer production are available and promising solutions. Not only do the farmers eliminate costs of waste treatment but can potentially attain further profit from products of employed technologies. The main aim of this research is to analyse and evaluate the current situation of waste management in a small agri-food production company, Agro GTV, and propose sustainable innovative solutions on how to improve its biowaste management with the application of circularity measures, to reduce costs and increase the efficiency of waste management based on the research and new developments in the area.